Evaluation of sepsis using compensatory reserve measurement: A prospective clinical trial. Issue 2 (August 2020) - Benov, Avi; Brand, Anat; Rozenblat, Tal; Antebi, Ben; Ben-Ari, Anat; Amir-Keret, Rotem; Nadler, Roy; Chen, Jacob; Chung, Kevin K.; Convertino, Victor A.; Paran, Haim
Abstract : BACKGROUND: Sepsis, a leading cause of morbidity and mortality worldwide, characterized by metabolic and hemodynamic changes that can lead to multiorgan failure and death. The evaluation of a patient's condition is routinely performed by several objective criteria. The compensatory reserve measurement (CRM) represents a new paradigm that measures the total of all physiological compensatory mechanisms, using noninvasive photoplethysmography to read changes in arterial waveforms. The present study's aim was to evaluate the applicability and the predictive value of the CRM during sepsis. METHODS: Data were prospectively collected from patients hospitalized in the department of surgery because of different inflammatory illnesses. All subjects were evaluated with hemodynamic, laboratory measurements and CRM throughout hospitalization. RESULTS: Of 100 subjects enrolled, 84 patients were not septic. The remaining 16 patients were in sepsis (Sequential Organ Failure Assessment [SOFA] score, >2), 6 of whom were in septic shock and 4 died. When nonseptic patients were compared with septic patients, statistical differences were found in C-reactive protein level ( p < 0.0005), SOFA score ( p < 0.0005), and CRM ( p < 0.0001). Other parameters did not show any difference between groups. The area under the receiver operating characteristic curve for CRM was 1, significantly higher than the area under the receiver operating characteristic for heart rate (0.78), systolic blood pressure (0.67), quick SOFA (0.81), and respiratory rate (0.56). CONCLUSION: Clinical criteria, imaging, and laboratory features used to identify a septic patient are suboptimal. This demonstrates the need for a monitoring device capable of detecting rapidly, constantly, and simply the sum condition of the ill patient. We have shown that CRM was able to distinguish between severe septic and nonseptic patients early in the course of hospitalization and was significantly more sensitive than the conventional diagnostic tools. Such capability to assess the septic patients or even to triage these patients will surely aid treatment of sepsis. LEVEL OF EVIDENCE: Care management, level II.